2019
DOI: 10.14295/jmphc.v10i0.334
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos epidemiológicos, clínicos e assistenciais da monitorização hemodinâmica invasiva: uma revisão bibliográfica

Abstract: A monitorização hemodinâmica refere-se à monitorização invasiva do sistema arteriovenoso, utilizado para medir pressões intracardíacas, intrapulmonares, intravasculares e também para determinar a eficácia da terapia. Este estudo objetivou identificar os aspectos epidemiológicos, clínicos e assistenciais da monitorização invasiva, bem como seus tipos. Trata-se de um estudo descritivo, documental e de revisão bibliográfica. A amostra foi composta por 18 artigos compreendidos entre 1984 a 2016 na qual abordava a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…Hemodynamic monitoring refers to invasive monitoring of the arterial and venous system, used to measure intracardiac, intrapulmonary, and intravascular pressures and to determine the effectiveness of therapy. Despite the rapid advancement of non-invasive monitoring techniques, invasive hemodynamic monitoring is essential in ICUs (da Silva et al, 2019;Ramos et al, 2008;Dias et al, 2006) Invasive hemodynamic methods are also essential in defining PH. Recent studies have shown that, even with lower mPAP values, there is an increase in mortality rates (Maron et al, 2016) In December 2018, a consensus resulting from the 6 th World Symposium on Pulmonary Hypertension redefined PH to a situation where mPAP is greater than 20 mmHg and pulmonary vascular resistance is greater than or equal to 3 Wood units (Calderaro, et al, 2019;Simonneau et al, 2014;Simonneau et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemodynamic monitoring refers to invasive monitoring of the arterial and venous system, used to measure intracardiac, intrapulmonary, and intravascular pressures and to determine the effectiveness of therapy. Despite the rapid advancement of non-invasive monitoring techniques, invasive hemodynamic monitoring is essential in ICUs (da Silva et al, 2019;Ramos et al, 2008;Dias et al, 2006) Invasive hemodynamic methods are also essential in defining PH. Recent studies have shown that, even with lower mPAP values, there is an increase in mortality rates (Maron et al, 2016) In December 2018, a consensus resulting from the 6 th World Symposium on Pulmonary Hypertension redefined PH to a situation where mPAP is greater than 20 mmHg and pulmonary vascular resistance is greater than or equal to 3 Wood units (Calderaro, et al, 2019;Simonneau et al, 2014;Simonneau et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Professionals must be able to select and carry out the most appropriate monitoring methods according to the individual needs of patients, considering the risk-benefit balance of the techniques. Monitoring data mean nothing if they are not added to physical findings and critically analyzed by nurses (Da Silva et al, 2019;Azevedo & Oliveira, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Porém, devem ser avaliados diariamente quanto a sua permanência visando desinvadir o paciente o mais breve possível para evitar complicações adicionais. 18 Nessa perspectiva, obtiveram-se como três principais desfechos dos pacientes deste estudo infecção, VM >48h e LRA, respectivamente. Mesmo ofertando o suporte técnico e tecnológico na assistência em UTI ainda são frequentes desfechos desfavoráveis aos pacientes durante a internação.…”
Section: Discussionunclassified
“…Revisão integrativa sobre os aspectos epidemiológicos, clínicos e assistenciais da monitorização não invasiva mostrou que esse cuidado é caracterizado como um dos mais importantes no atendimento de pacientes neurocríticos. Atualmente, é possível detectar e analisar uma grande variedade de sinais fisiológicos através de diferentes técnicas, invasivas e não invasivas (SILVA et al, 2019). O enfermeiro deve ser capaz de selecionar e executar o método de monitorização mais apropriado de acordo com as necessidades individuais do paciente, considerando a relação risco-benefício da técnica.…”
Section: Discussionunclassified